Analisis Sistem Informasi Akuntansi Terhadap Pengeluaran Kas Pada PT PP (Persero) TBK (Proyek Trans Sumatera Tol Indrapura-Kisaran) - Faiz Mukaffi Achmadi; Arnida Wahyuni Lubis (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
In the current era of globalization, technological developments are progressing rapidly, one example is accounting information systems, the large amount of expenditure for production and operational costs means that companies must be able to pay attention to this so that the desired things do not happen. In this research, researchers used qualitative methods based on library research. The results of this research indicate that PT. PP (Persero) Tbk (Trans Sumatra Indrapura-Kisaran Toll Road Project) has been implemented systematically and in accordance with the accounting system, as well as the cash disbursement accounting recording system which is effective and efficient. The company's internal control system for cash disbursements has been implemented well, and everyone in each unit has worked together to improve the cash and disbursement systems after the finance department discovered recording errors. This shows that there is a strong level of internal control implemented in each department, making it difficult to misappropriate and embezzle funds.